Pengukuran Servant Leadership Sebagai Alternatif Kepemimpinan di Institusi Pendidikan Tinggi Pada Masa Perubahan Organisasi - Handoyo, Seger (UI Scholars Hub, 2010)
Leadership is a critical factor for organizational effectiveness and also has great influence to almost all human life. Higher education has a distinctive characteristics, so it needs a particular leadership. Recently, higher education in Indonesia is actively making organizational change, so higher education’s leaders continually make efforts to accomplish successful and significant change. The purposes of research are to examine how important is virtues of servant leadership and to examine multidimensionality of servant leadership. Result shows that servant leadership is an alternative of leadership to accomplish successful organizational change in higher education. Result also finds that servant leadership is a unidimensional construct.